Analysis of chemical components and biological activities of essential oils from black and white pepper (Piper nigrum L.) in five provinces of southern China. (January 2020) - Li, Yong-xin; Zhang, Chi; Pan, Shenyuan; Chen, Lei; Liu, Man; Yang, Kunlong; Zeng, Xiaobin; Tian, Jun
Abstract: The chemical composition and antioxidant and antifungal activities of hydro-distilled essential oils (EOs) in black and white Piper nigrum L were evaluated in the present study. Hydro-distilled EOs obtained from black and white P. nigrum L from five areas of China was analyzed by gas chromatography-mass spectrometry (GC-MS). Nineteen compounds were identiﬁed, accounting for 98.20–99.35% of the oils. Chemical variation in the oils was estimated using systematic cluster analysis and principal component analysis. Moreover, antioxidant activity was determined by DPPH and ABTS radical cation scavenging assay, ferric reducing power assay, and ferric ion chelating activity assay, scavenging superoxide anion free radical activity assay and antifungal activity were assessed by micro-well dilution assay. Our results suggest that the region of origin greatly inﬂuences the pepper's chemical composition and bioactivities, which might support the development and utilization of this promising bio-resource in food industries. Highlights: The chemical composition of EOs in black and white Piper nigrum L was analyzed. The chemical variation of EOs in black and white Piper nigrum L was evaluated. EOs from black and white Piper nigrum L exhibit significant antioxidant capacity. EOs from black and white Piper nigrum L exhibit significant antifungal capacity. EOs from Piper nigrum L may be used as new antioxidants or fungicides.